Mossbauer investigation of the photoexcited spin states and crystal structure analysis of the spin-crossover dinuclear complex [{Fe(bt)(NCS)(2)}(2)bpym] (bt=2,2'-bithiazoline, bpym=2,2'-bipyrimidine). - Gaspar, AB; Ksenofontov, V; Reiman, S; Gütlich, P; Thompson, A; Goeta, A; Muñoz, M; Real, J (2006)
The crystal structure of the complex [{Fe(bt)(NCS)(2)}(2)bpym] (1) (bt=2,2'-bithiazoline, bpym=2,2'-bipyrimidine) has been solved at 293, 240, 175 and 30 K. At all four temperatures the crystal remains in the P space group with a=8.7601(17), b=9.450(2), c=12.089(3) A, alpha=72.77(2), beta=79.150(19), gamma=66.392(18) degrees , V=873.1(4) Angstrom(3) (data for 293 K structure). The structure consists of centrosymmetric dinuclear units in which each iron(II) atom is coordinated by two NCS(-) ions in the cis position and two nitrogen atoms of the bridging bpym ligand, with the remaining positions occupied by the peripheral bt ligand. The iron atom is in a severely distorted octahedral FeN(6) environment. The average Fe--N bond length of 2.15(9) Angstrom indicates that compound 1 is in the high-spin state (HS-HS) at 293 K. Crystal structure determinations at 240, 175 and 30 K gave a cell comparable to that seen at 293 K, but reduced in volume. At 30 K, the average Fe--N distance is 1.958(4) Angstrom, showing that the structure is clearly low spin (LS-LS). At 175 K the average Fe--N bond length of 2.052(11) Angstrom suggests that there is an intermediate phase. Mössbauer investigations of the light-induced excited spin state trapping (LIESST) effect (lambda=514 nm, 25 mW cm(-2)) in 1 (4.2 K, H(ext)=50 kOe) show that the excited spin states correspond to the HS-HS and HS-LS pairs. The dynamics of the relaxation of the photoexcited states studied at 4.2 K and H(ext)=50 kOe demonstrate that HS-HS pairs revert with time to both HS-LS and LS-LS configurations. The HS-LS photoexcited pairs relax with time back to the ground LS-LS configuration. Complex [{Fe(0.15)Zn(0.85)(bt)(NCS)(2)}(2)bpym] (2) exhibits a continuous spin transition centred around 158 K in contrast to the two-step transition observed for 1. The different spin-crossover behaviour observed for 2 is due to the decrease of cooperativity (intermolecular interactions) imposed by the matrix of Zn(II) ions. This clearly demonstrates the role of the intermolecular interactions in the stabilization of the HS-LS intermediate state in 1.